Optimization of strawberry disinfection by fogging of a mixture of peracetic acid and hydrogen peroxide based on microbial reduction, color and phytochemicals retention - Van de Velde, Franco (2016)
The fogging of strawberries using a environmentally friendly sanitizer mixture of peracetic acid (5%) and hydrogen peroxide (20%) was performed in a model chamber and modeled as a function of the concentration (3.4, 20.0, 60.0, 100.0 and 116.6 µL sanitizer L−1 air chamber) and the treatment time (5.7, 15.0, 37.5, 60.0 and 69.3 min). The sanitizer fogging was adequate for reducing total mesophilic microbial and yeasts and moulds counts of fruits until seven days of storage at 2℃. However, sanitizer oxidant properties adversely affected the content of total anthocyanins, total phenolics, vitamin C, and antioxidant capacity to various degrees, with some deleterious changes in the fruits color, depending on the fogging conditions. A multiple numeric response optimization was developed based on 2.0 log microbiological reduction, maximum phytochemicals and antioxidant capacity retentions, with no changes in the fruits color, being the optimal fogging conditions achieved: 10.1 µL sanitizer L−1 air chamber and 29.6 min. The fogging of strawberries at these conditions may represent a promising postharvest treatment option for extending their shelf-life without affecting their sensory quality and bioactive properties.